Innate Immune Reconstitution in Humanized Bone Marrow-Liver-Thymus (HuBLT) Mice Governs Adaptive Cellular Immune Function and Responses to HIV-1 Infection - Garcia-Beltran, Wilfredo F.; Claiborne, Daniel T.; Maldini, Colby R.; Phelps, Meredith; Vrbanac, Vladimir; Karpel, Marshall E.; Krupp, Katharine L.; Power, Karen A.; Boutwell, Christian L.; Balazs, Alejandro B.; Tager, Andrew M.; Altfeld, Marcus; et al. (Frontiers in Immunology, 2021)
Humanized bone marrow-liver-thymus (HuBLT) mice are a revolutionary small-animal model that has facilitated the study of human immune function and human-restricted pathogens, including human immunodeficiency virus type 1 (HIV-1). These mice recapitulate many aspects of acute and chronic HIV-1 infection, but exhibit weak and variable T-cell responses when challenged with HIV-1, hindering our ability to confidently detect HIV-1–specific responses or vaccine effects. To identify the cause of this, we comprehensively analyzed T-cell development, diversity, and function in HuBLT mice. We found that virtually all HuBLT were well-reconstituted with T cells and had intact TCRβ sequence diversity, thymic development, and differentiation to memory and effector cells. However, there was poor CD4+ and CD8+ T-cell responsiveness to physiologic stimuli and decreased TH1 polarization that correlated with deficient reconstitution of innate immune cells, in particular monocytes. HIV-1 infection of HuBLT mice showed that mice with higher monocyte reconstitution exhibited greater CD8+ T cells responses and HIV-1 viral evolution within predicted HLA-restricted epitopes. Thus, T-cell responses to immune challenges are blunted in HuBLT mice due to a deficiency of innate immune cells, and future efforts to improve the model for HIV-1 immune response and vaccine studies need to be aimed at restoring innate immune reconstitution.